2005
DOI: 10.1542/peds.2004-2428
|View full text |Cite
|
Sign up to set email alerts
|

Exercise With and Without an Insulin Pump Among Children and Adolescents With Type 1 Diabetes Mellitus

Abstract: ABSTRACT. Background. The use of insulin pumps is becoming a popular technique for insulin delivery among patients with type 1 diabetes mellitus (T1DM), but there is no consensus regarding the guidelines for proper pump use during exercise.Objective. To investigate the physiologic responses and risk of hypoglycemia among children and adolescents with T1DM when exercising with the pump on (PO) (50% of the basal rate) or pump off (PF).Methods. Ten subjects with T1DM (6 female subjects and 4 male subjects), 10 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 25 publications
(25 reference statements)
4
74
1
3
Order By: Relevance
“…The real-time availability of CGM data may have also contributed to the relatively low rates of early-and lateonset hypoglycemia. 14,15 Comparing days before versus after morning exercise sessions, we observed an increase in the CGM readings in the euglycemic range, showing the benefits of exercise on glycemic control. When we compared CGM data in days pre-and post-afternoon exercise, this was not evident, but we observed a clear tendency toward more hypoglycemic events.…”
Section: Discussionmentioning
confidence: 76%
“…The real-time availability of CGM data may have also contributed to the relatively low rates of early-and lateonset hypoglycemia. 14,15 Comparing days before versus after morning exercise sessions, we observed an increase in the CGM readings in the euglycemic range, showing the benefits of exercise on glycemic control. When we compared CGM data in days pre-and post-afternoon exercise, this was not evident, but we observed a clear tendency toward more hypoglycemic events.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, the authors of this study concluded that treatment with 15 g of oral glucose may be often insufficient to control exercise-induced hypoglycemia in adolescent patients. In contrast, Admon et al [7] did not observe any beneficial effects of physical exercise in patients with type 1 diabetes mellitus who exercised with insulin pumps or without. Furthermore, their patients, especially those using insulin pumps, more often presented with late hypoglycemia than hypoglycemia during exercise.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, their patients, especially those using insulin pumps, more often presented with late hypoglycemia than hypoglycemia during exercise. Therefore the authors recommended to turn off the pump during prolonged exercise, and to monitor blood concentration of glucose for several hours post-exercise, regardless of the pump type [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uno de los grandes beneficios del uso de tecnología en diabetes es la disminución de la HS o inducida por ejercicio [24][25][26] , especialmente cuando se utiliza SAPT con sistema de suspensión automática de la infusión frente a hipoglicemia [27][28][29] . Se recomienda el uso de SAPT, con o sin suspensión automática de insulina, en aquéllos sujetos en que los episodios de HS sean recurrentes y/o no manifiesten síntomas 30 .…”
Section: Reducción De Los Episodios De Hipoglicemia Severa (Hs)unclassified